An Anisotropic Convection-Diffusion Model Using Tailored Finite Point Method for Image Denoising and Compression (Communications in Computational Physics, 2020)
In this paper we consider an anisotropic convection-diffusion (ACD) filterfor image denoising and compression simultaneously. The ACD filter is discretizedby a tailored finite point method (TFPM), which can tailor some particular propertiesof the image in an irregular grid structure. A quadtree structure is implemented forthe storage in multi-levels for the compression. We compare the performance of theproposed scheme with several well-known filters. The numerical results show that theproposed method is effective for removing a mixture of white Gaussian and salt-and-peppernoises.